THE DEVELOPMENT OF ILLUSTRATED-STORY TELLING TEACHING MATERIAL BASED ON MAJALENGKA LOCAL WISDOM TO IMPROVE STUDENTS' CRITICAL THINKING SKILL - Irma Sofiasyari; Isna Amanaturrakhmah; Ike Kurniawati (Universitas Majalengka, 2024)
The analysis, design, development, implementation, and evaluation in this research represent the ADDIE development model, involving eight elementary school teachers and fourth-grade students from two elementary schools in Majalengka. The researchers used purposive sampling techniques. The research sample includes model schools, an independent curriculum, similar facilities and infrastructure, and accreditation A. This study uses interviews, questionnaires, and critical thinking questions to collect data. Data analysis is carried out through several steps, namely data reduction, data collection, data presentation, and drawing conclusions. Needs analysis, development of teaching materials, validation of teaching materials by expert validators, revision, and implementation are stages of research. The implementation was carried out in two schools, with each having a control class and an experimental class. The focus of this research is the validity and impact of illustrated story teaching materials on students' critical thinking skills. The results indicate that the teaching materials are suitable for use in learning because they meet the criteria of being very valid, with content feasibility at 83.15%, language at 86.1%, and graphics at 86%. The experimental group has an N-gain score of 0.743, while the control group has a score of 0.348, which falls into the low category. It can be said that the subject matter of illustrated stories based on the local wisdom of Majalengka has the potential to enhance students' critical thinking skills. Keywords: Teaching Material, Pictorial Book, Local Wisdom Analisis, desain, pengembangan, implementasi, dan evaluasi pada penelitian ini merupakan jenis pengembangan ADDIE dengan melibatkan delapan guru sekolah dasar dan siswa kelas empat dari dua sekolah dasar di Majalengka. Peneliti menggunakan teknik purposive sampling. Sampel penelitian termasuk sekolah percontohan, kurikulum merdeka, sarana dan prasarana yang sama, dan akreditasi A. Penelitian ini menggunakan wawancara, angket, dan soal berpikir kritis untuk mengumpulkan data. Analisis data dilakukan melalui beberapa langkah, yaitu pengurangan data, pengumpulan data, penyampaian data, dan penarikan Conclusion. Analisis kebutuhan, pembuatan bahan ajar, validasi bahan ajar oleh validator Expert, revisi, dan implementasi adalah tahapan penelitian. Implementasi dilakukan di dua sekolah, dengan kelas kontrol dan eksperimen masing-masing. Fokus penelitian ini adalah validitas dan dampak bahan ajar cerita bergambar terhadap kemampuan berpikir kritis siswa. Hasil penelitian menunjukkan bahwa bahan ajar layak digunakan dalam pembelajaran karena memenuhi kriteria Extremely valid dan memiliki tingkat kelayakan isi 83,15%, kebahasaan 86,1%, dan kegrafikan 86%. Kelompok eksperimen memiliki nilai N-gain 0,743, sedangkan kelompok kontrol memiliki nilai 0,348, yang menunjukkan Categories rendah. Sehingga dapat dikatakan bahwa materi pelajaran cerita bergambar yang didasarkan pada kearifan lokal Majalengka memiliki potensi untuk meningkatkan kemampuan siswa untuk berpikir kritis. Kata Kunci: Bahan ajar; Cerita bergambar; Kearifan Lokal